2021
DOI: 10.1002/cmdc.202000763
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Improved Guanidine‐Based Rac1 Inhibitor with in vivo Activity against Non‐Small Cell Lung Cancer

Abstract: The Rho GTPase Rac1 is involved in the control of cytoskeleton reorganization and other fundamental cellular functions. Aberrant activity of Rac1 and its regulators is common in human cancer. In particular, deregulated expression/activity of Rac GEFs, responsible for Rac1 activation, has been associated to a metastatic phenotype and drug resistance. Thus, the development of novel Rac1‐GEF interaction inhibitors is a promising strategy for finding new preclinical candidates. Here, we studied structure–activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…In HCC mouse model, 1D-142 was found to significantly reduce tumor growth and intrahepatic metastasis (193). Similarly, in mouse models of NSCLC, 1D-142 was found to inhibit NSCLC cell proliferation and migration by reducing Rac1-mediated TNFa-induced NF-kB nuclear translocation (192).…”
Section: General Rac1 Inhibitormentioning
confidence: 94%
See 1 more Smart Citation
“…In HCC mouse model, 1D-142 was found to significantly reduce tumor growth and intrahepatic metastasis (193). Similarly, in mouse models of NSCLC, 1D-142 was found to inhibit NSCLC cell proliferation and migration by reducing Rac1-mediated TNFa-induced NF-kB nuclear translocation (192).…”
Section: General Rac1 Inhibitormentioning
confidence: 94%
“…It has been found that 1A-116 and its parental compound ZINC69391 can inhibit the proliferation, invasion, migration, and cell cycle of BC cells, glioma cells, and leukemia cells, and 1A-116 shows higher specificity and intensity in vivo and in vitro (190,191). 1D-142 is a newly discovered new guanidine inhibitor, which can inhibit the activation of Rac1 by interfering with the interaction of Rac1-Tiam1, and its effectiveness in vivo and in vitro is much higher than that of the reported derivative 1A-116 (192). In HCC mouse model, 1D-142 was found to significantly reduce tumor growth and intrahepatic metastasis (193).…”
Section: General Rac1 Inhibitormentioning
confidence: 96%
“…The expression and activation of Rac1 has frequently been found to enhance the production of pro-inflammatory cytokines (IL-1β, but also IL-6, IL-8 and TNFα) in different pathological situations [ 102 , 103 ]. For example, the Rac1-GEF interaction inhibitor 1D-142 reduces the nuclear translocation of the transcription factor NFκB induced by the cytokine TNFα in NSCLC cells, and this activity contributes significantly to the antitumor effect of this guanidine-type Rac1 inhibitor in vivo [ 104 ]. Rac1 can interact directly with specific cytokines, such as IL-37, which controls the membrane translocation of the protein and its signaling activities, at least in lung adenocarcinoma [ 105 ].…”
Section: Rac1 In Bladder Cancermentioning
confidence: 99%
“…For instance, Rac1 Inhibitor CAS 1177865-17-6, a cell-permeable, reversible inhibitor of Rac1 GDP/GTP exchange, interferes with the interaction between Rac1 and Rac-specific GEFs [ 51 ]. More recently, Ciarlantini and colleagues identified a new family of chemical inhibitors against Rac1–GEF interaction that exhibited significant anti-proliferative activities in vitro and in a lung cancer animal model [ 52 ]. Furthermore, inhibitors have been developed that exhibited dual effects against Rac1 as well as Cdc42.…”
Section: Discussionmentioning
confidence: 99%